SOCIALIZATION OF PREVENTION OF KIDNEY FAILURE IN THE SIMPANG TIGA HEALTH CENTER WORKING AREA ACEH BESAR - Aditya Candra; Tahara Dilla Santi; Zurriyani; Andri; Ika Waraztuty; Farid Bastian; Said Aandy Saida; Muhammad Yani; Fuadi (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
Kidney failure has become a serious problem for public health in the world. This population increase is due to the lack of public awareness of living a healthy lifestyle and the increasing incidence of diseases which are risk factors. The aim of this activity is to provide information in the form of education to the public regarding kidney failure. Method: This community service activity was carried out in the work area of ​​the Simpang Tiga Health Center, Aceh Besar Regency. The number of participants was 30 people who were health cadres and community leaders. This activity includes counseling and discussion. The results of Community Service Activities (PKM) provide information and knowledge about kidney failure. Healthy living behaviors that are still not implemented include lack of exercise, consumption of instant food and packaged drinks. This habit has been understood by the public as a risk factor for kidney failure. Conclusion: Increased risk factors from a history of disease and less healthy living behavior need to be of concern to all related parties, namely individuals, community leaders/health cadres, and related government institutions, especially community health centers as primary health service locations that carry out promotive and preventive efforts. It is necessary to identify two historical diseases that are risk factors for kidney failure, namely diabetes mellitus and hypertension